2020
DOI: 10.21203/rs.3.rs-66750/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implications of COVID-19 on The of Fine Particulate Matter (PM2.5) in Ethiopia

Abstract: Background: The novel coronavirus pandemic, namely COVID-19, has become a global public health problem. COVID-19 was first reported in Ethiopia on 14 March 2020 by WHO. This paper is aimed at identifying the implication of COVID-19 on the concentration of PM2.5 from March 14, 2020 to July 31, 2020 in Ethiopia. Methods: The study gathered the environmental data released by Addis Ababa Central monitoring station before and during the coronavirus pandemic and discusses its impact on air quality. Daily concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…First, COVID-19 affected air pollution in different ways: in many cities, the lockdown triggered lower vehicular traffic and industrial emissions (He et al, 2020); after the transition to partial relaxation, these concentrations often returned to prepandemic levels (Rybarczyk and Zalakeviciute, 2021). The situation is different in AA, where available research suggests that PM2.5 concentration was higher during the pandemic (March-July 2020) compared to prior months (October 2019-March 2020), primarily due to the lack of lockdown measures (Bulto et al, 2020). Second, it is important to note that long-term exposure to air pollution affected COVID-19 related mortality: for example, a study from Harvard Chan School of Public Health found that a 1 µg/m 3 increase in air pollution was associated with an 11 percent increase in mortality from COVID-19 infection in the United States (Wu et al, 2020).…”
Section: Quantify the Impacts Of Ambient Pm25 On Morbiditymentioning
confidence: 95%
“…First, COVID-19 affected air pollution in different ways: in many cities, the lockdown triggered lower vehicular traffic and industrial emissions (He et al, 2020); after the transition to partial relaxation, these concentrations often returned to prepandemic levels (Rybarczyk and Zalakeviciute, 2021). The situation is different in AA, where available research suggests that PM2.5 concentration was higher during the pandemic (March-July 2020) compared to prior months (October 2019-March 2020), primarily due to the lack of lockdown measures (Bulto et al, 2020). Second, it is important to note that long-term exposure to air pollution affected COVID-19 related mortality: for example, a study from Harvard Chan School of Public Health found that a 1 µg/m 3 increase in air pollution was associated with an 11 percent increase in mortality from COVID-19 infection in the United States (Wu et al, 2020).…”
Section: Quantify the Impacts Of Ambient Pm25 On Morbiditymentioning
confidence: 95%